2014
DOI: 10.5603/ep.2014.0024
|View full text |Cite
|
Sign up to set email alerts
|

Markery ryzyka rozwoju cukrzycy typu 1 u krewnych I stopnia osób chorych na cukrzycę typu 1

Abstract: Introduction: The aim of this study was to evaluate beta-cell function and insulin resistance in relation to the occurrence of anti-islet antibodies in first degree relatives of patients with type 1 diabetes (T1D). Material and methods:The group studied consisted of 90 relatives and 60 healthy individuals without a family history of diabetes. An intravenous glucose tolerance test (IVGTT) was performed in all participants and the first phase insulin response index (FPIR) was calculated. Serum concentrations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In further support of the notion that β cell susceptibility may contribute to the development of T1D, a number of studies have analyzed insulin secretion in aAb-relatives of T1D index cases and found varying degrees of β cell dysfunction (21)(22)(23). While these data suggest the possibility that T1D kindreds may have preexisting impairments in β cell function, they also highlight one potential limitation of our control group.…”
Section: L I N I C a L M E D I C I N Ementioning
confidence: 57%
“…In further support of the notion that β cell susceptibility may contribute to the development of T1D, a number of studies have analyzed insulin secretion in aAb-relatives of T1D index cases and found varying degrees of β cell dysfunction (21)(22)(23). While these data suggest the possibility that T1D kindreds may have preexisting impairments in β cell function, they also highlight one potential limitation of our control group.…”
Section: L I N I C a L M E D I C I N Ementioning
confidence: 57%
“…In contrast to T2DM, which is a relative insulin deficient state with the pathology attributed largely to insulin resistance, it is a defect in insulin secretion that is the principal pathology of both HNF1A-MODY mutation carriers and T1DM [ 41 ]. This defect predates the clinical manifestation of diabetes as demonstrated by research in the carriers of HNF1A-MODY who were normoglycaemic and likewise in islet antibody positive relatives of those with T1DM [ 42 , 43 ]. We can hypothesize that the altered miR-224 expression profile may be a contributor to the beta-cell dysfunction noted in both HNF1A-MODY mutation carriers and T1DM.…”
Section: Discussionmentioning
confidence: 99%